Caterpillar Climbing: Robust, Tension-Based Omni-Directional Locomotion. Issue 3 (6th June 2018) - Vaughan, Samuel C; Lin, Huai-ti; Trimmer, Barry A
Abstract: Animals that must transition from horizontal to inclined or vertical surfaces typically change their locomotion strategy to compensate for the relative shift in gravitational forces. The species that have been studied have stiff articulated skeletons that allow them to redistribute ground reaction forces (GRFs) to control traction. Most also change their stepping patterns to maintain stability as they climb. In contrast, caterpillars, most of which are highly scansorial, soft-bodied, and lack rigid support or joints, can move with the same general kinematics in all orientations. In this study, we measure the GRFs exerted by the abdominal prolegs of Manduca sexta (Linnaeus) during locomotion. We show that, despite the orthogonal shift in gravitational forces, caterpillars use the same tension-based environmental skeleton strategy to crawl horizontally and to climb vertically. Furthermore, the transition from horizontal to vertical surfaces does not seem to require a change in gait; instead gravitational loading is used to help maintain a stance-phase body tension against which the muscles can pull the body upwards.